PEMBELAJARAN MATEMATIKA BERMUATAN KONSTRUKTIVISTIK UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA SEKOLAH MENENGAH PERTAMA - Tapilouw, Marthen (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2010)
It was hope that the improvement of mathematical reasoning should be reach by the students after the mathematics learning process, although it is not easy to reach. This study was carried out in secondary high schools through quasi experiment methods. The aim of this study is to describe: Students‟ achievement after the learning process, and the difficulties factors on learning mathematics, through contextual teaching and learning based on constructivist approach. The conclusions of this study are: The improvement of students‟ mathematical reasoning is quite good. There are also some positive improvements on students‟ autonomous learning, students‟ participation on the class discussion, the students‟ ability on answering the question, and the students can explain to the class how to solve the problems. The obstacle of the learning process is the number of students in the class and the learning schedule. The alternative way to overcome this problem is by giving work sheets to be done as home work or some activities out of the class. It was hope that in the future, the math book should be revised, and being adapted to contextual learning with contextual illustration that is well known and well understood by the learners, so mathematical lesson will be attractive and easy to learn.